2020
DOI: 10.1186/s12940-020-0565-4
|View full text |Cite
|
Sign up to set email alerts
|

Road proximity, air pollution, noise, green space and neurologic disease incidence: a population-based cohort study

Abstract: Background: Emerging evidence links road proximity and air pollution with cognitive impairment. Joint effects of noise and greenness have not been evaluated. We investigated associations between road proximity and exposures to air pollution, and joint effects of noise and greenness, on non-Alzheimer's dementia, Parkinson's and Alzheimer's disease and multiple sclerosis within a population-based cohort. Methods:We assembled administrative health database cohorts of 45-84 year old residents (N~678,000) of Metro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 74 publications
7
124
0
Order By: Relevance
“…Another study analyzed both traffic noise and road 470 proximity and reached a similar conclusion [122].…”
mentioning
confidence: 74%
“…Another study analyzed both traffic noise and road 470 proximity and reached a similar conclusion [122].…”
mentioning
confidence: 74%
“…Interestingly, from our result, the risks of PM 2.5 on AD had a nonnegligible decline since 2019. With per 5 g/m 3 PM 2.5 increase, the OR of AD declined 9%, when another indicated that with per 1.54 g/m 3 PM 2.5 increase, the OR of AD dropped 10% [33,37]. We speculated it might result from the low PM 2.5 concentrations in these two countries (regions) (4.1 and 19.7 g/m 3 ) and benign health care services.…”
Section: Mechanisms Of the Association Between Pm And Admentioning
confidence: 86%
“…The use of proxies and surrogates is a legitimate and common practice in epidemiological research ( 31 , 32 ), whenever objective data on the exposure and/or outcome of interest is not available, which is the case. On the other hand, in environmental and spatial epidemiology, geographic proximity to emission sources (e.g., major roads, industries) is commonly used as a proxy measure of personal exposure to air pollutants and\noise ( 33 , 34 ), under the assumption that individuals tend to spend their day within the home surroundings. Accordingly, it seems to us legitimate to assume that populations living near railway stations will be more likely to use them (i.e., to be exposed) than populations living far from railway stations.…”
Section: Discussionmentioning
confidence: 99%